Opportunity cost of natural forest management in the Arenal-Huetar Norte Conservation Area, Costa Rica. - Zúñiga-Méndez, Christian (2022)
[Introduction]: Part of the success of conservation programs is focused on the economic sustainability that they provide to the people who own the forests, within an increasingly aggressive productive landscape matrix. However, currently the economic relationship between land uses and their respective productive activities lacks empirical data to explain it. [Objective]: This study designed a model to evaluate the opportunity cost of forest management in natural forests, taking as a reference the primary productive activities that take place in its surroundings. [Methodology]: A data set of 24 sites with a forest management plan in natural forest, approved by the forest authorities of the Arenal-Huetar Norte Conservation Area, Costa Rica, was used. Likewise, geographic and productive information on alternative land uses was used. [Results]: With these data, an opportunity cost map was generated, which shows a marked segregation of the forests into 2 main zones: a) high opportunity cost zone, located to the south of the study area, with a range of $1,000.0 to ≥ $4,000.0 ha-1 yr-1; and b) medium zone and zone of low cost of opportunity, to the center-north of the site of interest, with a range of ≤ $0 to $1 000.0 ha-1 year-1. [Conclusions]: It is concluded that, at present, the ideal areas for timber harvesting are restricted to places far from the market and characterized by their low opportunity cost.